Pengaruh Current Ratio (CR), Debt To Equity Ratio (DER), Net Profit Margin (NPM) dan Earning Per Share (EPS) Terhadap Harga Saham Perusahaan Konstruksi & Bangunan yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2013-2017 - Jenni Suryana; Indra Widjaja (Universitas Tarumanagara, 2019)
This research aims to find out the effects of Current ratio (CR), Debt to equity ratio (DER), Net profit margin (NPM) dan Earning per share (EPS) toward stock price of the construction and building company which is listed in Indonesia Stock Exchange during 2013-2017.Sampling technique used is purposive sampling with criteria as (1) construction and building company which is listed in Indonesia Stock Exchange over the period from 2013 to 2017; (2) construction and building company who provided financial reports during 2013-2017; (3) Sample company still operate during research periods from 2013-2017. Based on this criteria, 9 samples were acquired. Data used in this research is secondary data obtained from www.idx.co.id and www.finance.yahoo.com. While the method of analysis used in this research is a method of regression anaylsis of panel data with fixed effect model.The result of this study show that CR and DER don’t have significant impact to the stock price of building and construction company; NPM and EPS have a significant price on stock price of building and construction company. Prediction capability of these four variables toward stock price is 92.29% as indicated by adjusted R square value, where the rest 7.71% is affected by others factors which was not entered to this research model.